Intracranial volume post cranial expansion surgery using 3D CT scan imaging in children with craniosynostosis - Sulong, Shukriyah (2019)
Background: Craniosynostosis is a congenital defect that cause one or more suture to fuse prematurely. Cranial expansion surgery which consist of cranial vault reshaping with or without fronto-orbital advancement (FOA) is done to correct the skull to a more normal shape of the head as well as to increase the intracranial volume. Therefore, it is important to evaluate the changes of intracranial volume (ICV) after the surgery and the effect of surgery both clinically and radiologically. Objective: This study is to (1) evaluate the ICV in primary craniosynostosis patients after the cranial vault reshaping with or without fronto-orbital advancement and to compare between syndromic and non-syndromic synostosis group, (2) to determine factors that associated with significant changes in the ICV postoperative, and (3) to evaluate the resolution of copper beaten sign and improvement in neurodevelopment after the surgery. Method: A prospective observational study of all primary craniosynostosis patients who underwent operation cranial vault reshaping with or without FOA in Hospital Kuala Lumpur from January 2017 until Jun 2018. The ICV preoperative and postoperative was measured using the 3D CT imaging and analysed. The demographic data, clinical and radiological findings was identified and analysed. Result: 14 cases (6 males and 8 females) with 28 3D CT scan were identified. The mean age of patients was 23 months. The patients were 7 syndromic synostosis (4 Crouzon syndrome and 3 Apert syndrome) and 7 were non-syndromic synostosis. The mean preoperative ICV was 880 mL (range, 641-1234 mL) while the mean postoperative ICV was 1081 mL(range,811-1385 mL) The difference was 201 mL which was statistically significant (P<0.001). In comparison, the mean volwne increment for syndromic synostosis and non-syndromic synostosis were 282 rnL and 120 rnL respectively. The difference was statistically significant (P<0.004). Mc Nemar's test was used to analyse pre and post-operative changes within the same patients. At 3 months post-surgery, all 13 patients with copper beaten sign pre-operatively did not show complete resolution on 3D CT imaging. Therefore the p-value was insignificant (P> 1.0). While 2 patients with neurodevelopmental delay pre-operatively showed no improvement during assessment at 3 months post-surgery. Again the p-value was insignificant (P> 1.0). Hence, there were no significant resolution in copper beaten sign and improvement in neurodevelopmental delay in this study. Conclusion: Surgery m craniosynostosis patients increases the intracranial volume besides it improves the shape of the head. From this study, the syndromic synostosis had better increment of intracranial volume compared to non-syndromic synostosis.